Supervisors’ Assessment According to Bost Method in a Chosen Polish Company - Konstanciak, Manuela; Borkowski, Stanisław; Jagusiak-Kocik, Marta (Communications - Scientific letters of the University of Zilina, 2011)
The main subject of the research presented in this paper is assessment of Polish supervisors with use of 4E+1P principle, 12 golden rules and Toyota’s principles. This is a part of research conducted within the confines of BOST method, based on the rules of Toyota’s system. This test method can be successfully used both in production and service institutions. There are two versions of the survey questionnaire: for supervisors and staff. The questionnaire includes also: the most important areas of improvement, visual control of factors, elements of the manufacturing process, competitive products, assessment of the supervisors and manufacturing processes. The results of research are presented as tables and bar charts.